Arna's children - Khamis, Juliano Mer; Danniel, Danniel; Trabelsi, Osnat; Huystee, Pieter van; Trabelsi Productions (Palestine : Trabelsi Productions, 2003)
A film that offers a rare and poignant window into the lives and deaths of a lost generation of Palestinian.'Arna's children', shows the life of Palestinian's children under Arna Mer Khamis and also the establishment of theatre, the Jenin Freedom Theatre in 2006
Title of accompanied DVD : The Jenin freeedom theatre today
Title from title screen
DVD format
Keywords: Children, Palestinian Arab; Palestine; Arab-Israeli conflict